Electrophoretic and immunochemical studies of Micrurus venoms - Alape Girón, Alberto (1994)
The electrophoretic mobilities of venom components from 15 Micrurus species were studied by polyacrylamide gel electrophoresis. The venoms showed species-specific protein patterns under native (PAGE) or denaturing (urea-PAGE) conditions. However, electrophoretic patterns obtained by SDS-PAGE under reducing conditions were similar. The proteins of all venoms had mol. wts either in the range of 45 to 75 kDa or lower than 14.5 kDa. PAGE and urea-PAGE of single extraction venom samples from 22 M. nigrocinctus nigrocinctus specimens revealed some proteins completely conserved, whereas others exhibited intraspecies variation. Based on ELISA cross-reactivity studies with 11 monoclonal antibodies against M. n. nigrocinctus venom, venoms from M. n. nigrocinctus, M. nigrocinctus mosquitensis, M. fulvius fulvius, M. dumerilii carnicauda and M. albicinctus were included in the same antigenic group, whereas M. frontalis frontalis and M. frontalis braziliensis venoms constituted a second group. Micrurus alleni and M. spixii spixii showed reactivity patterns similar to groups 1 and 2, respectively. Venoms from M. surinamensis surinamensis, M. corallinus, M. ibiboboca, M. hemiprichii ortoni, M. lemniscatus helleri and M. mipartitus had unique cross-reactivity patterns with monoclonal antibodies against M. n. nigrocinctus venom.